Probability Distribution of Arm Trajectory for Motion Estimation and Gesture Recognition - Wan Khairunizam, Wan Ahmad (American Scientific Publishers, 2013)
Link to publisher's homepage at http://www.ingentaconnect.com/content/asp/asl